2019
DOI: 10.1155/2019/3787696
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Extrafollicular Variant of Adenomatoid Odontogenic Tumor in the Maxillary Posterior Region

Abstract: Background. Adenomatoid odontogenic tumor (AOT) is a relatively uncommon benign neoplasm of odontogenic epithelial origin, accounting for less than 5% of odontogenic tumors. Case Report. The reported case describes morphological characteristics, clinical course, radiographic and histopathological features, and surgical therapy of an extrafollicular variant of AOT in the maxillary posterior region. An asymptomatic swelling on the left side in the posterior region of the maxilla, gradually increased since approx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Oral cancer is one of the most impacting oncological diseases; it can develop on oral and maxillofacial tissues [ 53 , 61 , 62 ]. Oral squamous cell carcinoma (OSCC) represents 2% of all oral tumors; nevertheless, it has a much higher proliferation rate than the other tumors affecting the oral cavity [ 63 ].…”
Section: Tumoroids In Oral Cancer Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral cancer is one of the most impacting oncological diseases; it can develop on oral and maxillofacial tissues [ 53 , 61 , 62 ]. Oral squamous cell carcinoma (OSCC) represents 2% of all oral tumors; nevertheless, it has a much higher proliferation rate than the other tumors affecting the oral cavity [ 63 ].…”
Section: Tumoroids In Oral Cancer Researchmentioning
confidence: 99%
“…Further studies have reported that organoids from induced pluripotent stem cells (iPSCs) organoids can grow with a limited development in size and morphology. In more detail, MSCs and iPSCs can be differentiated using similar protocols [62], but iPSCs-derived organoids do not reproduce the exact morphology and histology observed in adult tissues: this means that iPSCs-derived organoids may not be able to properly reproduce physiology and pathological characteristics of primary tissues, thus representing an unreliable tissue model. This concept particularly applies to lung cancer, where the use of iPSCs cells, rather than MSCs directly harvested from cancer, would seem to be an issue that makes such tumoroids not useful in cancer research [75][76][77].…”
Section: Current Limitations Of Organoidsmentioning
confidence: 99%